Digital climate advisory and bundled services (DCAS) tools landscape assessment for Bangladesh - Khanam, Fahmida; Amjath-Babu, Tharayil Shereef; Krupnik, Timothy J.; Giles, James Edward (2022)
This document is a long list of existing digital tools and platforms for selected value chains in Bangladesh based on key characteristics, accomplishments, challenges and business models.